1997
DOI: 10.1021/jp970460n
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Typical Solvolytic Reactions in SDS and TTABr Water-in-Oil Microemulsions

Abstract: The kinetics of the solvolysis reactions of diphenylmethyl chloride, 4-nitrophenyl chloroformate, benzoyl chloride, anisoyl chloride, and bis(4-nitrophenyl)carbonate were studied in isooctane/SDS/1-hexanol/water and isooctane/TTABr/1-hexanol/water microemulsions with a constant [1-hexanol]/[surfactant] ratio of 5. The results were interpreted by means of a pseudophase model for (isooctane + hexanol)/(surfactant + hexanol)/water systems, the distribution of hexanol between isooctane and surfactant being calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…The model was successfully applied to reactions that are catalyzed by b-CD [5,6] and those that are not. [7] In both cases we observed a significant quantity of uncomplexed b-CD in equilibrium with the micellar system and the absence of interactions between b-CD and the micelles once these have been formed. Here we present the results of a study on the basic hydrolysis of m-nitrophenylacetate (m-NPA) in micelle ± b-CD mixed systems of dodecyltrimethylammonium bromide (LTABr), trimetyltetradecylammonium bromide (TTABr), and trimethyloctadecylammonium chloride (OTACl).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The model was successfully applied to reactions that are catalyzed by b-CD [5,6] and those that are not. [7] In both cases we observed a significant quantity of uncomplexed b-CD in equilibrium with the micellar system and the absence of interactions between b-CD and the micelles once these have been formed. Here we present the results of a study on the basic hydrolysis of m-nitrophenylacetate (m-NPA) in micelle ± b-CD mixed systems of dodecyltrimethylammonium bromide (LTABr), trimetyltetradecylammonium bromide (TTABr), and trimethyloctadecylammonium chloride (OTACl).…”
mentioning
confidence: 67%
“…less, space group P1 Å (no. 2), a 8.9501 (7), b 12.4181 (6), c 15.7582 (10) , a 88.342(4), b 83.656 (6), g 71.097 (5)8, V 1646.8(2) 3 , Z 2, 1 1.964 g cm À3 , m(Mo Ka ) 7.13 mm À1 . A total of 10 787 reflections were measured at 150 K on a CAD4T/rotating anode diffractometer (l 0.71073 ) and averaged in a unique set of 7569 reflections (R av 0.036).…”
mentioning
confidence: 99%
“…As a co-surfactant, 1-hexanol stabilizes the micellar system, reduces interfacial polarity and thereby also tends to reduce the rates of solvolysis reactions taking place at the water-surfactant interface. 20 This paper describes the determination of iodine using the RMM-CL reaction of luminol in a chloroform-free micellar medium of CTAC dissolved in 1-hexanol-cyclohexane mixture. Four component systems of surfactant, co-surfactant (generally a short chain alcohol), oil and water have many important features and are the most studied microemulsion systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the solvolysis of anisoyl chloride was found to always be faster in cationic microemulsions (TTABr/hexanol/ isooctane/water), TTABr being tetradecyltrimethylammonium bromide, than in the case of anionic ones (SDS/hexanol/ isooctane/water); also, the k + /k -ratio increased with decreasing water content in the microemulsion. 21 This effect can be ascribed to the release of the leaving group, Cl -, being more favorable in the presence of cationic TTABr headgroups than in that of anionic SDS headgroups. By contrast, Bunton et al 22 found the k + /k -ratio in aqueous micelles to be only 0.1.…”
Section: Discussionmentioning
confidence: 99%